2018
DOI: 10.1159/000488686
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Silver Diamine Fluoride in Preventing Caries in the Primary Dentition: A Systematic Review and Meta-Analysis

Abstract: Objectives: To investigate whether silver diamine fluoride (SDF) is effective in preventing new caries lesions in primary teeth when compared to placebo or active treatments. Methods: Systematic review (CRD42016036963) of controlled clinical trials. Searches were performed in 9 electronic databases, 5 registers of ongoing trials, and reference lists of identified review articles. Two researchers carried out data extraction and quality appraisal independently. The primary outcome was the difference in caries in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
125
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 134 publications
(156 citation statements)
references
References 27 publications
14
125
0
17
Order By: Relevance
“…In their recent systematic review and metaanalysis, Oliveira and colleagues 49 evaluated caries prevention for primary teeth and concluded that, when compared with placebo at 24 months or more, SDF decreased the development of dentin caries lesions in treated and untreated primary teeth with a preventive fraction of 77.5%. Comparisons between SDF and FV concluded that SDF performed significantly better than FV at 18 and 30 months, and comparison between SDF and glass ionomer cements (GIC) showed that GIC was better than SDF at 12 months (not statistically significant).…”
Section: Current Evidence On the Efficacy Of Silver Diamine Fluoride mentioning
confidence: 99%
“…In their recent systematic review and metaanalysis, Oliveira and colleagues 49 evaluated caries prevention for primary teeth and concluded that, when compared with placebo at 24 months or more, SDF decreased the development of dentin caries lesions in treated and untreated primary teeth with a preventive fraction of 77.5%. Comparisons between SDF and FV concluded that SDF performed significantly better than FV at 18 and 30 months, and comparison between SDF and glass ionomer cements (GIC) showed that GIC was better than SDF at 12 months (not statistically significant).…”
Section: Current Evidence On the Efficacy Of Silver Diamine Fluoride mentioning
confidence: 99%
“…Oliveira et al 11 in a systematic review and meta-analysis evaluated the effectiveness of SDF in preventing caries in primary dentition compared to placebo, fluoride varnish, or no treatment. They concluded that SDF appears to prevent caries effectively in the complete primary dentition.…”
Section: Sdf In Caries Prevention Of Primary Dentitionmentioning
confidence: 99%
“…13,22,26 However, for a cumulative effect of silver uptake and risk of silver poisoning to occur, a total lifetime silver exposure of 1 g, corresponding to nearly 400 SDF applications is needed as per the U.S. Environmental Protection Agency. 49 Another concern is the black discoloration 10,11,34,40 in the arrested lesions disclosed after SDF application (Figs 2B and 3B). Parents and children should be informed that SDF application causes black or dark brown stain, as the soft infected dentin turns harder and development of a sclerotic black surface in the tooth.…”
Section: Points Of Concern Related To Sdfmentioning
confidence: 99%
See 1 more Smart Citation
“…The third systematic review looked at SDF use for prevention of caries in primary teeth. 227 This review included 2 trials comparing SDF with no treatment, one comparing SDF with a placebo and NaF varnish and the other comparing SDF with glass ionomer cement. The conclusions were that SDF appears to effectively prevent new caries development when compared with no treatment, placebo, or fluoride varnish.…”
Section: Silver Diamine Fluoridementioning
confidence: 99%